Identification of pathogenic variants in the ABCG2 gene in patients with severe familial hyperuricemia and gout - Toyoda, Yu; Pavelcova, Katerina; Masinova, Jana; Hasikova, Lenka; Zavada, Jakub; Hanova, Petra; Klein, Martin; Vavra, Jiri; Takada, Tappei; Stiburkova, Blanka (Molecular and cellular biochemistry, 2025)
We report the identification of two pathogenic variants in the ABCG2 gene, encoding a urate exporter, in two probands (male and female) with severe familial gouty phenotypes and hyperuricemia. Clinico-genetic analyses identified p.I63YfsTer54 (rs565722112) and p.G74D (rs199976573) as potentially causal mutations; functional analyses demonstrated that these two variants are deficient in plasma membrane localization and functionally null. Our data show that dysfunctional variants in the ABCG2 gene are strong risk factors for hyperuricemia and gout in both males and females.
Keywords: mutace; ABC transportér z rodiny G, člen 2; ATP Binding Cassette Transporter, Subfamily G, Member 2; Urate transport; Female; dna (nemoc); ABCG2; ženské pohlaví; hyperurikemie; lidé; Gout; Mutation; Hyperuricemia; Male; Aged; nádorové proteiny; Neoplasm Proteins; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans